Correlation of DC and AC electrical properties of Al/p-Si structure by I-V-T and C(G/ω)-V-T measurements - Ozdemir, Orhan; Tatar, Beyhan; Yilmazer, Deneb; Gokdemir, Pinar; Kutlu, Kubilay (ELSEVIER SCI LTD, 2009)
Current-voltage-temperature and admittance-gate bias-temperature measurements were performed on Al/p-Si structure to investigate transport and storage properties. In forward direction of former measurement, three distinct voltage regions designated different transport mechanisms: recombination, tunneling and space charge limited current. In the reverse direction, current seemed to be roughly proportional to the square root of bias at low region. Activation energy (E-A) as 0.56 eV together with the ideality factor around 1.5 confirmed that generation-recombination current was the actual current transport mechanism. Increase in applied bias resulted in the appearance of other mechanisms: tunneling and space charge limited current, deduced by temperature-independent current flow and power of bias (greater than 2) in both forward and reverse directions, respectively. On the other hand, the distinctive bias voltage regions in current-voltage-temperature measurement corresponded to inverting, depleting and accumulating gate bias regimes in typical M(I)S structure for admittance analysis. Conductance branch of admittance reflected a similar behavior with that of the measurement under both temperature and frequency as parameter. On the other hand, with the aid of capacitance branch of admittance in the light of mentioned regimes and their corresponding energy band diagrams, correlation with ac and dc electrical properties was carried out. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Current mechanisms; Admittance; Deep depletion; Surface band bending; SCHOTTKY-BARRIER DIODES; MIS TUNNEL-DIODES; CRYSTALLINE SILICON HETEROJUNCTIONS; VOLTAIC ENERGY-CONVERSION; CURRENT TRANSPORT; LOW-TEMPERATURES; FILM; CAPACITANCE; MECHANISM; Engineering; Materials Science; Physics